Analysis of Increasing Women's Participation in 2018 Governor Election in Maleer Village, Bandung, West Java - Ana Sabhana Azmy; M. Ricky Ridestian (Universitas Medan Area, 2021)
This article aims at analyzing the participation and behavior of women voters in the 2018 West Java Governor Election in Maleer Village, Bandung City. The study was conducted qualitatively, supported by primary data in observations and interviews with several sources. Secondary data was obtained from searching for several references, either through books, journals, or other supporting data. The results of this study showed that the participation of women in the 2018 West Java governor election was 79.16%, higher than the participation of men at 74.26%. Several factors encouraged women to exercise their right to vote in the 2018 West Java governor election in Maleer Village, Bandung City, referring to Myron Weiner's theory, namely modernization, modern mass communication, and conflicts between groups of political leaders. Modernization was followed by the more active involvement of women in public spaces, modern mass communication, that female voter used mass media technology as a preference in voting, and an increase in identity politics has occurred since the 2017 DKI Jakarta Regional Head Election. It has had an impact on the 2018 Governor Election. There was polarization in society. In terms of voting behavior, women in Maleer Village chose figures based on psychological choices and rational choices. The psychological selection of female voters on candidate figures was based on social media for governor candidates as a means of interaction with the community. Meanwhile, the rational choice of female voters was based on looking at the program or work of a candidate for governor who was an incumbent figure (previously serving). Women assess what impact they have had while the candidate for governor (who was the incumbent) was in office and find out whether previous programs have been beneficial or not for them as a woman.